Consistent estimation of global VAR models - Jan Mutl (Institute for Advanced Studies (IHS), 2009)
In this paper, I propose an instrumental variable (IV) estimation procedure to estimate global VAR (GVAR) models and show that it leads to consistent and asymptotically normal estimates of the parameters. I also provide computationally simple conditions that guarantee that the GVAR model is stable.
Keywords: C31; C32; C33; 330; global VAR; GVAR; consistent estimation; instrumental variables; VAR-Modell; Zeitreihenanalyse; Modellierung